Microfluidic-Assisted Nanoprecipitation to Produce Personalised Dosage Forms - Hosseini, Sarvenaz (2022)
The rise of polypharmacy and knowledge of pharmacogenetics has the potential to revolutionise dosing regimens for patients. Already, many single nucleotidepolymorphisms have been identified as cause for alternate dosing in particular patient populations. Current manufacturing techniques in the pharmaceutical industry fall short on producing on demand, personalised, and patient tailored dosage forms. During this study, we propose that personalised multiparticulate drug delivery systems encompassing both nanoparticles and microparticles, produced through on-demand microfluidic-assisted production methods could help integrate current and future therapeutics for geriatric patients with high pill burdens. Microfluidic assisted particle production enables the user to have greater control on particle size through flow rate ratios and chip design along with traditional parameters already used in the field of polymeric nanoprecipitation such as solvent choice, polymer concentration, polymer characteristics and surfactant use. Through the application of this technology to drugs of different biopharmaceutical class types, this project aims to introduce the microfluidic platform as a strategy to produce ‘on demand’ personalised dosage forms. Currently, the project is using the FDA approved Poly(lactic-co-glycolic acid) (PLGA), a biocompatible and biodegradable polyester. Particle sizes of 80 nm to 400 nm have been achieved by using a 190 µm droplet junction microfluidic device. At polymer concentration of 2.5 mg/mL particle size was increased from 74 nm ± 1.6 nm to 128nm ± 1.3 nm through reducing continuous phase flow rate while keeping the polymer phase flow rate constant. Similar size control was observed at all concentrations studied except where agglomeration and consequent chip blockages resulted in unreliable results. Altering the polymer phase to aqueous phase flow ratio within the microfluidic system as well as reducing polymer concentration helped prevent blockages, however resulted in an overall reduced particle size with all the samples collected having a PDI < 0.15. A ‘levelling off’ of particle size is observed at which point NP size does not alter significantly even with changing flow rates and concentrations when mixing conditions are optimal. The model drug chosen is the dihydropyridine calcium channel blocker Nifedipine for encapsulation with PLGA. Future works include release studies and surface analysis techniques to characterise Nanoparticles.